STRATEGI BUMDES DALAM PENGEMBANGAN WISATA SAWAH SUMBER GEMPONG DI KABUPATEN MOJOKERTO - Alviana Ramadhani; Nabilla Choirunnissah; Diani Ayu Hanif; Mohammad Musleh (Journal of Contemporary Public Administration, 2024)
The purpose of this study was to analyze and describe the strategy of BUMDES Mutiara Welirang in developing tourism in Sawah Sumber Gempong Tourism, Ketapanrame Village, Mojokerto Regency, in order to find out the problems that exist in tourism development through the role of the government and management. The approach taken in this study is a qualitative descriptive approach by conducting observations, interviews, and documentation. The data analysis model according to (Geoff Mulgan 2010)with data collection techniques, data reduction, data presentation, and drawing conclusions. The results of the study showed that first, the objectives implemented by BUMDES Mutiara Welirang in developing tourism in Sawah Sumber Gempong Tourism have been fulfilled and are running well because they have a significant impact on the economy of the community, especially the people of Ketapanrame village. Second, the community environment around Ketapanrame village also supports and plays an active role in the development of tourism in Sawah Sumber Gempong tourism, as evidenced by the community fully participating in the development of facilities and infrastructure in the Sawah Sumber Gempong tourism area and actively participating in maintaining the surrounding environment so that it is more beautiful and well maintained. Third, the intervention carried out by BUMDES Mutiara Welirang has been running efficiently. This can be seen from a number of strategic efforts that continue to be carried out by BUMDES Mutiara Welirang and the community groups that support development, such as by collaborating with stakeholders and banking companies. In addition, facilities and infrastructure continue to be developed to attract tourists and as a means of advancing tourism.